2013
DOI: 10.1155/2013/670451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Propolis Water Extract Using a Reliable RP-HPLC Methodology andIn VitroandIn VivoEfficacy and Safety Characterisation

Abstract: Since the beginning of propolis research, several groups have studied its antibacterial, antifungal, and antiviral properties. However, most of these studies have only employed propolis ethanolic extract (PEE) leading to little knowledge about the biological activities of propolis water extract (PWE). Based on this, in a previous study, we demonstrated the anti-inflammatory and immunomodulatory activities of PWE. In order to better understand the equilibrium between effectiveness and toxicity, which is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 40 publications
1
50
0
7
Order By: Relevance
“…Here, we evaluated PWE, PMM, and PSDE that were developed with higher concentrations of propolis dry matter, that is, around 11%, 50%, and 70% of genuine propolis extract. The antifungal results obtained for PWE were different when compared with the antibacterial results obtained by Rocha et al [37], and since undesirable results were found, PWE was not considered in the mucoadhesive preparations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Here, we evaluated PWE, PMM, and PSDE that were developed with higher concentrations of propolis dry matter, that is, around 11%, 50%, and 70% of genuine propolis extract. The antifungal results obtained for PWE were different when compared with the antibacterial results obtained by Rocha et al [37], and since undesirable results were found, PWE was not considered in the mucoadhesive preparations.…”
Section: Discussionmentioning
confidence: 81%
“…Considering some disadvantages of this presentation, the present work tried to study other options to use propolis in medicine, such as aqueous, microparticles, and soluble dry extract. Rocha et al [37] have demonstrated that it is possible to achieve aqueous propolis extract similar in chemical composition to the alcoholic ones, and Bruschi et al [38, 39] obtained gelatin microparticles with propolis, without taste, strong odour, and without the presence of alcohol. Here, we evaluated PWE, PMM, and PSDE that were developed with higher concentrations of propolis dry matter, that is, around 11%, 50%, and 70% of genuine propolis extract.…”
Section: Discussionmentioning
confidence: 99%
“…The employed method was fully validated as reported by Rocha et al [31]. The results for BC/propolis biomembranes A, B, and C, and the propolis standardized extract (EPP-AF) used, may be observed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…V79 cell cultures in vitro and mice treated with water extract of propolis in vivo presented no genotoxic effect in the micronucleus assay, which is used for the screening of genotoxic potential of both clastogens and aneugens (Rocha et al ., ). Similar results have been found with propolis hydroalcoholic extract using chromosomal aberrations assay in Chinese ovary hamster cells and Wistar rat bone marrow cells (Tavares et al ., , ).…”
Section: Biological Propertiesmentioning
confidence: 97%